Twin in compared with singleton pregnancies complicated by Preterm premature rupture of membranes (PPROM) - Mirzamoradi, Masoumeh; Baleshi, Maral; Rahmati, Nayereh; Hazari, Vajiheh; Daraei, Maedeh; Heidar, Zahra (Novelty in Biomedicine, 2020)
Background: Our purpose was to compare the latency periods of preterm premature rupture of the membranes (PPROM) in twin compared with singleton pregnancies from 24 to 34 weeks’ gestation and assessment of respiratory distress syndrome (RDS) between twins and singletons. Materials and Methods: Between 2010 and 2014 in Mahdieh Hospital, Tehran, Iran, data on all women with singleton and twin gestations complicated by PPROM were reviewed. Latencies between singleton and twin pregnancies were compared. An additional comparing according to PPROM at under, equal and above 30 weeks’ gestation was surveyed in these groups. In addition, their latencies compared among them. Use of surfactant consumption and need for intubation were measured during hospitalization between twins and singletons. Results: The mean latencies of singleton and twin pregnancies were statistically significant without comparing the gestational age at PPROM (8.22±7.4 vs. 5.54±3.36 days, p=0.001). When PPROM occurred at < 30 weeks’ gestation, latency in twins was not statistically significant (8.24±9.81 vs. 8.24±4.71 days, p=0.07) but at > or = 30 weeks’ gestation, latency was significantly different in singleton and twin pregnancies (6.3±5.85 vs. 2.42±2.60 days, p=0.002). There were significant differences in the use of surfactant and intubation between twin and singletons (p<0.05). Conclusion: This study provides the basis for effective patient counseling and managing pregnancies with PPROM. Overall, in pregnancies with PPROM at > or = 30 weeks’ gestation, latency in twins was significantly shorter than in singleton pregnancies. For fetal lung maturity, the use of surfactant and intubation increased in twins compared with singletons.